Audit System Information at The Language Muhammadiyah University of Sidoarjo - Muhammad Syauqil; Ade Eviyanti; Mochamad Alfan Rosid; Azmuri Wahyu Azinar (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2025)
This test was conducted to assess the performance of the information system of the Language Center at Muhammadiyah University Sidoarjo using the COBIT 5 DSS domain framework. The audit aimed to evaluate the reliability and efficiency of the system in addressing operational issues such as limited website access and failure to print TOEFL certificates. Data collection involved interviews with unit leaders and technical observations. The results showed varying maturity levels from 2.1 (DSS03) to 4 (DSS06). Critical findings included the absence of a ticketing system and backup automation. Recommendations focused on implementing centralized incident management and cybersecurity training. This study provides a governance model for optimizing language service systems in higher education institutions.